Dis-position, an art installation by Lutz-Rainer Müller and Stian Ådlandsvik ... - Campbell, Sandy (University of Alberta Library, 2024)
This art installation is located on the UiT The Arctic University of Norway campus in Tromsø, Norway. From the installation description, "This work consists of 10 lanterns from the cities with the 5 largest airports and the 5 largest container ports in the world, based on 2013 statistics. They point towards the cities they represent and have been oriented parallel to the lanterns in those cities. The lights turn on and off according to the sundown an sunrise in their places of origin. Dis-position visualizes the current - but soon to be outdated - junctions between geography and the world's economy, and questions Tromsø's positioning globally." Cities with the 5 largest airports in 2013: Hartsfield-Jackson Atlanta, Beijing Capital, London Heathrow, Tokyo, O'Hare Chicago. Cities with the 5 largest container ports in 2013: Shanghai, Singapore, Hong Kong, Shenzhen, Busan. ...